Contrasting Effects of Nitrogen Addition on Vegetative Phenology in Dry and Wet Years in a Temperate Steppe on the Mongolian Plateau - Zhou, Zhenxing; Zhang, Liwei; Liu, Yinzhan; Zhang, Kunpeng; Wang, Wenrui; Zhu, Junkang; Chai, Shijie; Zhang, Huiying; Miao, Yuan (Frontiers in Plant Science, 2022)
Changes in spring and autumn phenology and thus growing season length pose great challenges in accurately predicting terrestrial primary productivity. However, how spring and autumn phenology in response to land use change and nitrogen deposition and underlying mechanisms remain unclear. This study was conducted to explore the growing season length (GSL) and its components (i.e. the beginning (BGS) and ending of growing season (EGS)) in response to mowing and nitrogen addition in a temperate steppe on the Mongolia Plateau during two years with hydrologically contrasting condition (dry (2014) vs. wet (2015)). Our results demonstrated that mowing advanced the BGS only by 3.83 days, nitrogen addition advanced and delayed the BGS and EGS by 2.85 and 3.31 days, respectively, and thus prolonged the GSL by 6.16 days across the two growing seasons from 2014 to 2015. When analyzed by each year, nitrogen addition lengthened the GSL in the dry year (2014), whereas shortened it in the wet year (2015). Further analyses revealed that the contrasting nitrogen impacts on the GSL were attributed to monthly precipitation regimes and plant growth rate indicated by the maximum of normalized difference vegetation index (NDVmax). Moreover, changes in the GSL and its two components had divergent impacts on community productivity. The findings highlight the critical role of precipitation regimes in regulating the responses of spring and autumn phenology to nutrient enrichment and suggest that the relationships of ecosystem productivity with spring and autumn phenology largely depend on interannual precipitation fluctuations under future increased nitrogen deposition scenarios.